Menerapkan Filosofi STOA dalam Profesi Akuntansi untuk Pendidik - Feby Yolanda; Yolanda Ritonga, Anggie (Income Journal: Accounting, Management and Economic Research, 2023)
This research aims to see the harmony between the characteristics of Stoicism and the principles of educational accountants according to the IAI and how Stoic philosophical thinking can help educational accountants in implementing the code of ethics and principles of their profession. The role of an educational accountant is very unique because accounting not only focuses on knowledge but also learning how to behave ethically in accordance with the accounting profession. There are four virtues in stoicism, namely wisdom, justice, courage and simplicity. The reason why this core philosophy is useful and good to study and deepen is because it is not limited to age or background, anyone can practice it without having to think about whether he is rich enough, has academic achievements, different beliefs, innate intelligence, and so on. The research method of this paper is briefly a conceptual paper, first summarizing the research literature on the accounting teaching profession and then Stoic philosophy. The results of the discussion show that the steadfast nature that can help manage negative emotions, carrying out virtues (wisdom, justice, courage and self-control) can help the teaching and learning process of the accounting profession, develop yourself better as a teaching accountant and become a role model for prospective accountants and be able to properly apply the accounting professional code of ethics.